Penerapan Jaringan 5G Dalam Pengembangan Pembelajaran Daring Di Sekolah Dasar Hingga Tingkat Menengah - Fadhlirrahman Baso; Andi Muh Amar Ma'ruf (Sakura Digital Nusantara, 2023)
Online learning has weaknesses when internet services are weak, and lecturer instructions are poorly understood by students. Online learning is currently still constrained by an inadequate internet connection. Delays that are too large and connections that are not smooth or unstable on the internet network for online learning can be a problem, namely the occurrence of errors in receiving information. For this reason, there needs to be an increase in the performance of the communication system that is able to support online learning so that teaching and learning activities can take place properly. 5G technology has the potential to support this because of the several advantages it offers, including supporting speeds up to 10 times the current technology (4G). The research method used in this study uses a literature review. Literature review is research conducted by reviewing several literatures that are in accordance with the title of the research being discussed. Literature study is intended to summarize, analyze and interpret concepts and theories that are in accordance with the research conducted.